PENGELOLAAN LINGKUNGAN MELALUI PENGELOLAAN SAMPAH UPAKARA DI DESA KENDERAN, KECAMATAN TEGALLALANG, KABUPATEN GIANYAR - Made Novia Indriani; I Made Harta Wijaya; I Putu Gede Adi Gunawan; I Made Wira Putra Pratama (UNHI Press, 2023)
The Province of Bali is a major tourist destination in the world, in addition to natural beauty, customs, and ceremonies are a special attraction, Kenderan Village, which is located in Tegallalang District, Gianyar Regency, with its customs and people very often carry out ceremonial activities, but ceremonial waste and waste are an important problem in the area because it causes high waste generation and production, but currently there is no optimal waste management and processing. Through community service activities providing understanding related to environmental management through ceremonial waste management, by involving village officials and the local community to increase awareness about environmental cleanliness on an ongoing basis. The steps and stages of activities starting from sorting to making mixed roof tiles are carried out for the local community to empower them by utilizing the results of ceremonial waste/garbage to provide economic value. Based on these activities, the community gets significant benefits in raising awareness about cleanliness and managing the environment properly.